Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China - Peng, Yu; Wang, Hongzhu; Cui, Yongde (Zootaxa, 2017)
Four species of Tubificinae (Oligochaeta: Naididae), Tubifex laxus n. sp., Tubifex gracilentus n. sp., Tubifex conicus He, Wang & Cui, 2012, and Tubifex tubifex (Müller, 1774) are reported from Tibet, China. T. laxus n. sp. is distinguished from allied species by relatively wide atria. T. gracilentus n. sp. differs from congeners in extremely thin and long penial sheaths. T. conicus is redefined as a species that lacks spermathecae. T. tubifex as redescribed here has slightly hirsute hair chaetae, cuticle rings around the penes and spermathecae with empty ampullae.